Pertunjukan Kethoprak Ngesti Pandowo, 1950-1996 - Mahendra Pudji Utama; Dhanang Respati Puguh; Rabith Jihan Amaruli (Department of History, Faculty of Humanities, Diponegoro University, 2021)
The study about Ngesti Pandowo's kethoprak performance is always enchanting because not enough attention yet been got in various studies. This article discusses the Ngesti Pandowo's kethoprak performance in the period of the 1950s-1996 using the historical method. Kethoprak has been performed by Ngesti Pandowo since the early independence of Indonesia. In it’s heyday in the 1950-1970s, kethoprak had receded and only to provide entertainment to the audience in the different type. In the 1980s, Ngesti Pandowo began entered a receding period. Its prestige as a kitsch theater began faded because the the main artists died and was no successor. It was no more creative artists who capable becoming maecenas. In this situation, Ngesti Pandowo's kethoprak performances have actually increased and can be a salvage lid to keep getting viewers.